2013
DOI: 10.1016/j.jcs.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Variant high-molecular-weight glutenin subunits arising from biolistic transformation of wheat

Abstract: a b s t r a c tGenetic transformation via the biolistic method has been used to introduce genes encoding natural and novel high-molecular-weight glutenin subunits (HMW-GS) into wheat. The appearance of new seed proteins of sizes not predicted by the transgene coding sequences was noted in some experiments. In this report, the identities of thirteen of these novel proteins were determined by tandem mass spectrometry (MS/MS). Seven different proteins larger than and two proteins smaller than the native protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…It has been noted that allelic differences in the composition of HMW-GS and LMW-GS induce changes in the structure and properties of the glutenin polymers and, consequently, the baking quality (Payne et al 1987;Shewry et al 2003). The wheat genes that encode HMW-GS constitute 5 to 10% of the grain storage proteins and are related to the strength and elasticity of the dough (Shewry et al 2003;Blechl and Vensel 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that allelic differences in the composition of HMW-GS and LMW-GS induce changes in the structure and properties of the glutenin polymers and, consequently, the baking quality (Payne et al 1987;Shewry et al 2003). The wheat genes that encode HMW-GS constitute 5 to 10% of the grain storage proteins and are related to the strength and elasticity of the dough (Shewry et al 2003;Blechl and Vensel 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Glu-D1 locus has been reported as the one that has the greatest effect on the rheological properties and baking quality of the flour. The 5+10 alleles at this locus have been associated with flours with more suitable viscoelastic properties for bread making and that also result in bread with higher volume (Payne et al 1987;Luo et al 2001;Liang et al 2010;Li et al 2010;Hernández et al 2012;Blechl and Vensel 2013). Vázquez et al (2012) reported that 1 and 2* alleles at Glu-A1 are also associated with greater gluten strength and good baking quality, while Peña et al (2005) found that 17+18 and 7+8 alleles at Glu-B1 are also associated with high bread volume, especially the 17 allele, which has a positive effect on the rheological properties of the flour.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that Glu-D1 locus have significant influence to rheological and bread making quality. So, the HMW-GS subunit 1Ax1 and subunits pair 1Dx5+1Dy10 have the greatest relationships with flours with more suitable viscoelastic properties for bread making and that also result in bread with higher volume (Liang et al 2010;Hernández et al 2012;Blechl and Vensel, 2013). Also, other investigation showed that HMW-GSs such as 1Ax1, 1Ax2*, 1Bx7, and 1Bx17 + 1By18 have positive effects on dough characteristics, while 1AxNull, 1Bx20, 1Bx6 + 1By8, 1Dx2 +1Dy12 have negative effects on gluten quality and bread-making quality (Shewry et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some researchers have raised concerns that the transformation process could result in various unintended effects, which are unrelated to the nature of the specific transgene 14 15 16 . Although most event-specific effects are routinely eliminated during the early screening stages 17 , there are some reports of apparently normal transgenic plants exhibiting aberrant behavioral or biochemical characteristics upon further analysis 16 18 .…”
mentioning
confidence: 99%
“…Nevertheless, some researchers have raised concerns that the transformation process could result in various unintended effects, which are unrelated to the nature of the specific transgene 14 15 16 . Although most event-specific effects are routinely eliminated during the early screening stages 17 , there are some reports of apparently normal transgenic plants exhibiting aberrant behavioral or biochemical characteristics upon further analysis 16 18 . For example, higher lignin levels and composition were found in stems of the MON810 Novelis T and Valmont T varieties than their respective near-isogenic lines 19 , and unforeseen metabolic variations involving the primary nitrogen pathway were observed when comparing La73- Bt (MON810) and La73 (non-transgenic) 20 .…”
mentioning
confidence: 99%